2020
DOI: 10.3390/cryst10020061
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassical Nucleation and Crystallization

Abstract: Nucleation and growth are of uttermost importance for crystallization since they determine the structure, shape, and properties of a crystal [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
(18 reference statements)
1
18
0
Order By: Relevance
“…Although there were a few studies that focused on the spatiotemporal analysis of pattern formation, they overlooked the formation process of the single band, which is the basic unit of the pattern. ,, (3) Pattern formation has been considered a result of simple precipitation, ,,, which omits the complicated process where constituent precipitates are actually developed by the aggregation of primary particles larger than atoms/ions/molecules. Recently, an increasing number of discoveries have indicated that crystallization proceeds through the attachment of amorphous intermediate precursors. …”
Section: Introductionmentioning
confidence: 99%
“…Although there were a few studies that focused on the spatiotemporal analysis of pattern formation, they overlooked the formation process of the single band, which is the basic unit of the pattern. ,, (3) Pattern formation has been considered a result of simple precipitation, ,,, which omits the complicated process where constituent precipitates are actually developed by the aggregation of primary particles larger than atoms/ions/molecules. Recently, an increasing number of discoveries have indicated that crystallization proceeds through the attachment of amorphous intermediate precursors. …”
Section: Introductionmentioning
confidence: 99%
“…Adding water to the reaction mixture gives rise to COF-5 crystals with larger diameters by shifting the equilibrium from large oligomers towards monomers, thereby favoring lateral (pathway 1) over vertical growth (pathway 2). The crystallization of COF-5 is non-classical and similar to crystallization by particle attachment (CPA), [38][39][40] since oligomers are the key precursors in the nucleation process and dominate vertical growth. On the other hand, as opposed to the CPA mechanism, COF-5 crystallization involves several metastable species like oligomers and stacked structures in the nucleation process, different mechanisms in vertical and lateral growth, and simultaneous presence of the classical monomer-by-monomer addition mechanism that dominates the lateral growth of the COF-5 crystals.…”
Section: Figmentioning
confidence: 99%
“…Crystallization by particle attachment (CPA), a so called non‐classical crystallization mechanism, is known to form morphological and textural patterns that cannot be explained in the scope of classical nucleation and growth models. [ 8 ] This is not surprising as CPA is a multi‐step process where every step has its own intricate interplay between thermodynamic and kinetic constrains defining a very unique crystal growth pathway. As an example, crystallization by amorphous particle attachment involves the formation and stabilization of amorphous particles, their accretion and, finally, transformation into the crystalline phase.…”
Section: Introductionmentioning
confidence: 99%